Influencia del programa Juntos en el desarrollo social de la población en extrema pobreza del distrito de Agallpampa, periodo: 2014 – 2017 - Rodriguez Arteaga, Carlos Francisco (2019)
ABSTRACT The purpose of this research work is to determine the level of influence of the JUNTOS program in the extreme poverty population of the Agallpampa District during the last four years, under the social dimension of development. The research problem is formulated according to the following question: How does the JUNTOS program influence the social development of the extreme poverty population of the Agallpampa District, period: 2014 - 2017 ?; The hypothesis states that the JUNTOS program has a favorable influence on the social development of the extreme poverty population of the Agallpampa District, period: 2014 - 2017. The following stand out as study variables: Independent variable: JUNTOS Program; and, Dependent variable: Social Development of the population in extreme poverty. The descriptive design was used, as well as the following methods: deductive - inductive, analytical - synthetic, ethnographic and statistical. The population studied was made up of 722 extreme poor people of the Agallpampa District, from which a representative sample of 186 was established. The interview guide, questionnaire, program JUNTOS beneficiary’s registry was applied as data collection instruments of the Agallpampa District and National Household Survey, theses and web pages. The results show that the JUNTOS Program influences the population living in extreme poverty by changing their lifestyles, attitudes and way of thinking, with this they will improve in hygiene, safe water consumption, nutritious foods, cleaning in the house, etc., however, a part of the people interviewed and interviewed agree that the economic incentive should be increased, be careful in the enumeration of households, use strategies to determine the use of the economic incentive. The discussion of the results, allow establishing that the JUNTOS Program favorably influences the extreme poverty population of the Agallpampa District, improving the levels of education, health, identity and use of the economic incentive. The conclusions establish that the implementation of the JUNTOS Program will allow to improve the quality of life of the people, generate human capital, decrease the anemia rates, malnutrition, improve family income, consume nutritious food.